Foreign Debt and Exchnage Rate In Nigeria: The Stepwise Regreession - Osifalujo Babatunde Bunmi; Isiaka Najeem Ayodeji; Taiwo Oluwaseun Kayode (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
The considerable argument on the relationship between foreign debt and exchange rate remains debatable among the researchers. Various conclusion had been drawn with different methodology and variables considered in the existing studies. Therefore, this study investigated the relationship between foreign trade and exchange rate in Nigeria for the period of 30years between 1990 and 2019. The study relied on secondary source of data gathered through CBN statistical bulletin 2020 version. Foreign debt was strictly represented with multilateral debt, bilateral debt, Paris club and London club debt while exchange rate was considered as dependent variable. Stepwise regression and vargranger were considered for the analysis and revealed that multilateral debt, Paris club and London club debt are the major debt positively influencing exchange rate fluctuation while bilateral debt has a negative relationship. Also, multilateral debt, bilateral debt and London club debt have a significant impact on exchange rate compare to Paris club debt with insignificant impact on exchange rate. Various model analysed in the study shows Multilateral debt remains significant in the entire model while bilateral became insignificant in the model 4 and Paris club debt is not significant in Model 4 and 5. The granger causality test revealed that exchange rate does not influence multilateral debt but multilateral debt influences exchange rate. The study concluded that foreign debt has a significant relationship with exchange rate. Therefore, the study recommends government should maintain a favorable and controlled public external debt in order to reduce the exchange rate in Nigeria.